Synthesis, characterization and its photocatalytic activity of mesoporous sulfur-doped TiO2 nanocrystal aggregates for environmental applications - Kwan, Keith Shan Yao. (2012)
The sol-gel method was used to synthesize sulfur-doped TiO2 powder using potassium persulfate as the sulfur source. Mesoporous nanocrystal aggregates were successfully created. The aggregates were 100nm wide and were composed of smaller 10nm TiO2 nanocrystals. The synthesis parameters, namely calcination temperature and dopant amounts were varied to investigate the effects on morphology, surface area, phase composition and photocatalytic activity.400ºC was shown to be the optimum calcination temperature, allowing anatase crystals to form, whilst maintaining high surface area and mesoporosity. Higher amounts of dopant led to increased surface area and UV photocatalytic activity. The presence of peroxodisulfate anions may have been responsible for the generation of mesoporous structures. These anions were burnt off during drying or calcination, leaving spaces between the aggregates. The increased porosity led to higher surface area, allowing more sites for pollutant binding, contributing to higher photocatalytic efficiency. The incorporation of sulfate onto the TiO2 surface through doping could have led to the presence of S4+ and S6+ states. These states have significant potential to suppress the recombination of charge carriers thus further enhancing photocatalytic activity. Sulfur-doped TiO2 synthesized under the aforementioned conditions had UV activity that was 1.43 times that of P25 under UV 254nm and 1.87 that of P25 under UV 365nm.